The Malayan Landscape Paintings - Sarena Abdullah; Yuen Beng Lee (SPAFA Journal)
Landscape paintings were one of the earliest visual art renditions of the Malay land in Malaysia. Traveller artists who arrived in Malaya and Singapore during the 18th and 19th centuries illustrated various subject matters that they observed. The most common examples included tropical flora and fauna, various views and landscapes, British residences, and so on. The theme of a tremendously fertile land with beautiful natural resources and prosperous economic activities is among the few themes and representations that were drawn or painted by early Malayan artists in the early 20th century. Landscape can be considered the most significant and intrinsic pictorial form in modern Malaysian art, as it was one of the earliest mediums of visual impressions and expressions. This article explores the evolution of the representation of Malaysia in landscape paintings from the early 19th century to mid-20th century by examining selected works and discussing how these artistic renditions reflect the changes that were happening in Malaya, from the types of landscapes produced by British artist-officers to how the British government mooted the Malayan cultural strategy to gain public trust and confidence in their ability to combat insurgency. These could be seen as how art exhibitions and institutions, the encouragement of certain art-production through predominantly featured picturesque and peaceful landscapes, and portrayals that create a sense of calm and tranquillity amidst the violent climate of the Malayan Emergency were intended to alleviate anxieties and provide solace to the public.